German right-wing party AfD finds more support in rural areas with aging populations - Christian Franz; Marcel Fratzscher; Alexander S. Kritikos (DIW Weekly Report, 2018)
This study examines in which setting the German political party Alternative for Germany (Alternative für Deutschland, AfD) performed well in the 2017 parliamentary elections. The AfD's popularity was relatively high in electoral districts with an above-average amount of craft businesses, a disproportionately high amount of older residents and workers in the manufacturing sector, and - applicable mainly to western German electoral districts - where the disposable household income was lower than the national average. The unemployment rate in the electoral districts and the share of foreigners in the population affect the AfD's popularity to a lesser extent. Generally, the AfD performs better in rural areas with negative demographic trends - a phenomenon that occurs more frequently in eastern German districts than in western districts. This allows for the conclusion that perspective is lacking among those living in rural areas with negative demographic developments.
Keywords: D72; Z13; 330; German political parties; federal elections 2017; structural data